Influence of Teacher Perfomance Appraisal on Teacher Performance in public Secondary Schools - Aloo, Joash Okello (JOOUST, 2017)
Low teacher Performance in public secondary schools in Kenya remains the concern for the general public and Government. Teacher commitment in Kisii County has been unsatisfactory. This has been reflected by the relatively low students' performance in KCSE in Kisii County. This could have affected students' performance in national examinations, co-curriculum activities and even compromised students' discipline. The Teachers Service Commission (TSC) introduced Teacher Performance Appraisal (TPA) in 2012 to improve on teachers' performance in schools; this was a departure from armual confidential report that had been in place over the years. The purpose of this study was to examine the influence of TPA on teacher performance in public secondary schools in Kisii County, Kenya. The objectives of the study were to; determine the influence of TPA on timeliness in implementation of the curriculum; establish influence of TPA on effectiveness in curriculum evaluation in public schools; find out the influence of TPA on effectiveness in performance of administrative duties; establish the influence of TPA on effectiveness in management of students' discipline, explore the influence of TPA on effectiveness in organization of co• curricular activities and to establish the extent of implementation of TPA in public secondary schools. Discrepancy model was adopted to guide the study. The sequential triangulation design within the mixed method approach was used. The study population comprised 334 Principals, 5450 teachers and 334 Deputy Principals of public secondary schools and the TSC-County Director. Stratified random sampling technique was used to select 179 Principals and 179 Deputy Principals while Multi stage sampling for 30 teachers of public secondary schools and purposive sampling technique to select the TSC County Director of the county. Questionnaires were used to collect data from the Principals and Deputy Principals while key informant interview guide was used to collect information from TSC-County Director, Principals and teachers. Document analysis guide was used to collect data which was not readily obtained through questionnaires. Reliability of the instruments for data collection was tested by assessing the scale's internal consistency using Crobanch's alpha and reliability coefficient of at least 0.7 was achieved in all the sub-scales of the questionnaire. Validity was determined by experts in Educational Administration of Jaramogi Oginga Odinga University of Science and Technology. Quantitative data was analyzed by using descriptive and inferential statistics. Qualitative data from the respondents was analyzed for content as themes and sub-themes emerged. The study established that TPA policy had positive significant influence on; timeliness in curriculum implementation (r=.604, p<.05), curriculum evaluation by teachers (r =.726, p<.05), performance of administrative responsibilities (r =0.691, p<.05), management of students' discipline (r =.722, p<.05) and organization and supervision of co-curricular activities (r =.612, p<.05). The study established that TPA: accounted for 36.3% of the variation in timeliness in curriculum implementation; accounted for 52.5% of the variation in curriculum evaluation; accounted for 52.0% of the variation in management of students' discipline and accounted for47.7% of the variation in performance of administrative responsibilities; and it accounted for 3 7 .2% of the variation in organization and supervision of co-curricular activities by teachers in secondary schools. Subsequently, TPA was established to be a significant predictor of the variables: timelines in curriculum implementation [F (l , 316) = 181.90, p < .05]; curriculum evaluation [F (l , 316) = 351.92, p <.05)]; management of students' discipline [F (J, 316) = 343.81, p < .05); performance of administrative duties [F (1, 316) = 289.55, p < .05] and organization and supervision of co-curricular activities [F (I, 316) = 188.92, p < .05). The study concluded that TPA had positive influence on teacher performance. The study recommends that TSC should enforce TP A policy and use it as a tool for promoting and deploying teachers into leadership positions.
Keywords: Teacher Performance.; Teacher Performance Appraisal.; Teacher Performance in public Secondary Schools.; Kenya.